Do New Chiefs Mean Fresh Perspectives? The Institutionalization of the Police Executive Environment - Matusiak, Matthew C. (Criminal justice and behavior, 2021)
Research suggests policing is a highly institutionalized field. Limited attention has been paid, however, to the institutionalization of leaders’ views. Assessing turnover in 71 Texas police organizations between October, 2011, and July, 2015, this research evaluates whether there is consistency (i.e., institutional homogenization) after turnover in chiefs’ perceptions of their environments and agency priorities. The research is unique in that it assesses two chiefs’ perceptions that have both led the same law enforcement agency in successive time periods. Assessments of environment and priorities from former chiefs and those replacing them are evaluated utilizing descriptive, bivariate, and multivariate methods. These assessments are also compared with a control group of chiefs from agencies not experiencing turnover. Bivariate results suggest little variation across current and former chiefs, whereas ordinary least squares (OLS) regression models suggest differing relationships across chiefs groups between environmental perceptions and agency priorities. Discussion of the findings is framed by institutional theory.